PENERAPAN PRINSIP RULE OF LAW DALAM PELAYANAN PUBLIK PENERBITAN SIUP DI KOTA TANGERANG SELATAN - Agus Nugraha (Arena Hukum, 2019)
AbstractRule of law as one of the principles in the principle of good governance is the main pillar in ensuring the implementation of quality public service, including in the service of issuing a Trading Business License (SIUP). The Purpose of this research is to describe and analyze the application of the rule of law principle in the service of issuing SIUP by the Regional Governent of South Tangerang City. This research uses an empirical juridical method with qualitativ descriptive data analysis techniques. The results of the study show that the application of the rule of law principle in the public service of issuing SIUP in South Tangerang City is still not optimal. This is due to a vacuum of norms, namely the absence of regulation regarding the SIUP Issuance Service Standards which were prepared in a participatory manner in accordance with Act No. 25 of 2009 concerning Public Services.AbstrakRule of law sebagai salah satu prinsip dalam prinsip good governance merupakan pilar utama dalam menjamin terselenggaranya pelayanan publik yang berkualitas termasuk dalam pelayanan penerbitan Surat Izin Usaha Perdagangan (SIUP). Tujuan dari penelitian dalam artikel ini adalah untuk mendeskripsikan dan menganalisis penerapan prinsipÂ rule of law dalam pelayanan penerbitan SIUP oleh Pemerintah Daerah Kota Tangerang Selatan. Penelitian dalam artikel ini menggunakan metode yuridis empiris dengan teknik analisis data deskriptif kualitatif. hasil penelitan menunjukkan bahwa penerapan prinsipÂ rule of law dalam pelayanan publik penerbitan SIUP di Kota Tangerang Selatan masih belum maksimal. Hal tersebut disebabkan adanya kekosongan hukum (vacuum of norm) yakni belum adanya pengaturan mengenai Standar Pelayanan Penerbitan SIUP yang disusun secara patisipatif sesuai UU No.25 Tahun 2009 tentang pelayanan publik.